Utilization of agro-waste for mass production of Trichoderma asperellum to promote plant growth and control Fusarium wilt infection on tomato - A B Easa Hasan, Zainap (2020)
Chemical pesticides are commonly used for managing Fusarium wilt disease of tomato caused by Fusarium oxysporum f. sp. lycopersici. However, the use of chemicals can lead to ecological instabilities and the pathogen produces chlamydospores for survival in a dormant stage over a long period in the soil. Therefore, this present study was conducted to evaluate the in vitro and in vivo ability of Trichoderma spp. by formulating agro-waste to inhibit Fusarium wilt pathogen on a tomato plant. The screening of antagonistic Trichoderma isolates' potential against F. oxysporum f. sp. lycopersici was conducted under in vitro, while the efficacy of the selected isolate of Trichoderma to control the disease and promote growth was observed under in vivo conditions. Previously, Trichoderma species have been used as antagonists against different plant pathogens but recently, enhancing its efficacy becomes important. One-hundred and eighty-four isolates of Trichoderma were used in this study were originally isolated from soil. These isolates were obtained from the Mycology Laboratory, Faculty of Science, Universiti Putra Malaysia. Among 184 Trichoderma isolates tested to dual culture, six isolates showed a very high antagonistic activity based on the percentage inhibition of radial growth (PIRG) values against F. oxysporum f. sp. lycopersici, which were of Trichoderma asperellum isolates B1902 (81.23%), C1667 (80.27%), C1669 (79.41%), B2230 (78.35%) and T2007 (78.11%) as well as T. harzianum isolate C1675 (78.45%). Subsequently, three potential Trichoderma isolates (T. asperellum B1902, T. asperellum C1667 and T. harzianum C1675) were tested for their antibiosis properties through poison food agar assay. A maximum percentage of inhibition value (90.49%) was achieved at 80% culture filtrate concentration on metabolites of T. asperellum B1902 followed by T. asperellum C1667 and T. harzianum C1675, which gave 87.38% and 84.28%, respectively. This study continued on an evaluation of the best medium for T. asperellum mass and their micropropagule production. Trichoderma isolates were added to the seven types of media (topsoil, rice-bran, compost, coconut husk fiber, oil palm empty fruit bunch and biochar). All the isolates survived at different levels. Based on the colony-forming units (cfu) evaluation among the tested media, coconut husk was most suitable in promoting the sporulation of Trichoderma. The highest cfu was found in coconut fiber with T. asperellum (B1902) based formulation (9.053x105 ± 7.88 cfu/g) followed by oil palm empty fruit brunch with Trichoderma asperellum (B1902) based formulation (7.4Q6x105 ± 9.03 cfu/g). From this, the ability of the combination of T. asperellum B1092 with coconut fiber and oil palm empty fruit bunch to control the Fusarium wilt of a cherry tomato plant, as well as to promote plant growth was investigated in plant house and field conditions. Trichoderma asperellum B1092 reduced the severity of tomato Fusarium wilt and enhanced all plant growth parameters and quality of tomato. Total lycopene (122.30 g/kg), sugar (6.50%), K (4.22%), N (2.14%), Ca (0.14%), P (0.14%) and Mg (0.10%) contents in tomato fruits were significantly higher when inoculated with Trichoderma in coconut fiber. As a condusion, T. asperellum B1902 may offer the potential for biologically controlling Fusarium wilt of tomato and increasing the quality of the fruit.